Risk factors for infection with colistin-resistant gram-negative microorganisms: a multicenter study - Yilmaz, Gul R.; Dizbay, Murat; Guven, Tumer; Pullukcu, Husnu; Tasbakan, Meltem; Guzel, Ozlem Tunccan; Tasyaran, Mehmet A. (K Faisal Spec Hosp Res Centre, 2016)
BACKGROUND: Knowing risk factors for colistin resistance is important since colistin is the only remaining choice for the treatment of infections caused by multi-drug resistant microorganisms. OBJECTIVE: Evaluate risk factors associated with infection by colistin-resistant microorganisms. DESIGN: Retrospective study. SETTINGS: Tertiary healthcare centers. PATIENTS AND METHODS: An e-mail including the title and purpose of the study was sent to 1500 infectious disease specialists via a scientific and social web portal named Infeksiyon Dunyasi (Infection World). Demographic and clinical data was requested from respondents. MAIN OUTCOME MEASURE(S): Colistin-resistance. RESULTS: Eighteen infectious disease specialists from twelve tertiary care centers responded to the invitation. Data was collected on 165 patients, 56 cases (39.9%) and 109 (66.0%) age-and sex-matched controls. The colistin-resistant microorganisms isolated from cases were 29 Acinetobacter baumannii (51.8%), 18 Pseudomonas aeruginosa (32.1%) and 9 Klebsiella spp. Colistin, carbapenem, and quinolone use in the last three months were risk factors for colistin resistance in the univariate analysis. Previous quinolone use in the last three months (P=.003; RR: 3.2; 95% CI: 1.5-6,7) and previous colistin use in the last three months (P=.001; RR: 3.6; 95% CI: 1.63-7.99) were significant risk factors in the multivariate analysis. CONCLUSION: Clinicians should limit the use of quinolones and remain aware of the possibility of resistance developing during colistin use. LIMITATIONS: The lack of a heteroresistance analysis on the isolates. No data on use of a loading dose or the use of colistin in combination.
Keywords: 2-Component Regulatory System; Critically-Ill Patients; Klebsiella-Pneumoniae; Pseudomonas-Aeruginosa; Cystic-Fibrosis; Polymyxin-B; Acinetobacter; Susceptibility; Methanesulfonate; Heteroresistance